Shape Manifestation of Respiration in the Axial System - Eliška Slawiková; Monika Šorfová; Tereza Dolanská (Karolinum Press, 2014)
Shape Manifestation of Respiration in the Axial System The aim of the study was to evaluate the effect of respiration on the shape changes of the axial system. Our approach focuses more on the analysis of respiratory function and their implementation within the complex axial system - the trunk. The results of this pilot study will use as evidence for further study of relationship between respiration and physiotherapy. Now we are looking for an answer to the question, at what level of the human body reflected the influence of respiration and its use in physiotherapy. This pilot study was attended by two women and one man aged 25-40 years, who were not selected for the study according to predetermined conditions. The same characteristic features of all three prarticipants were sedentary job connected with excessive mental strain, occasional low back pain (usually after a long sitting) and the absence of acute or chronic respiratory diseases. Another common feature of the participants was the absence of structural changes in the spine. During the experiment was monitored maximum inhalation and maximum exhalation, and respiratory maneuver Kapalabhati, often used as one of the basic yoga breathing exercises. To detect trunk movement during the respiratory maneuver, we opted for a Qualysis - 3D torso topography. At the same time spirometer panned changes in volume over time, both exhaled and inhaled air. The purpose of this study was to assess symptoms and implementation of respiratory maneuvers in the axial system, particularly the chest and abdominal area. During the experiment, we followed the differences in reaction of the chest and abdomen in respiratory maneuver in the direction vertical, antero-posterior and lateral. The difference in these indicators at different phases of the respiratory maneuver confirms our assumption of the possibility of influencing the selected folders axial system through appropriately selected respiratory maneuver. After processing of the measurement results, we found a significant superiority of the realized movement in the abdomen compared to the chest region, although this is more a 3D movement, which is given by the kinematic motion of the ribs to the sides. Movement is therefore spatially complex. Spirometric evaluation of the identified volumes is consistent with the measured changes in the shape of the trunk. Overall, it is not necessary to evaluate the results statistically, but case reviews - compare always "formula" realization of the respiratory maneuver that person. Tvarové projevy respirace v rámci axiálního systému Cílem práce bylo zhodnotit vliv respirace na tvarové změny axiálního systému. Náš přístup se zaměřuje podrobněji na analýzu dechových funkcí a jejich realizaci v rámci komplexu axiální systém - trup. Výsledky této pilotní studie využijeme jako poznatky pro další studium vztahu respirace a fyzioterapie. Nyní hledáme odpověď na otázku, na jaké úrovni lidského těla se odrazí vliv respirace a její využití ve fyzioterapii. Této pilotní studie se zúčastnili dvě ženy a jeden muž ve věku 25-40 let, kteří nebyli vybráni do studie podle předem daných podmínek. Shodnými charakteristickými rysy všech 3 probandů bylo sedavé zaměstnání spojené s nadměrnou psychickou zátěží, občasnou bolestí bederní páteře (nejčastěji po dlouhodobém sezení) a absence akutního či chronického onemocnění dýchacích cest. Dalším společným prvkem účastníků byla absence strukturálních změn v oblasti páteře. V experimentu byl sledován maximální nádech a maximální výdech a také respirační manévr Kapalabhati, často používaný jako jeden ze základních jógových dechových cvičení. Pro detekci pohybu trupu během respiračního manévru jsme zvolily popis 3D topografie trupu metodou Qualisys. Zároveň byla spirometrem snímána změna objemů v čase, a to jak vydechovaného, tak nadechovaného vzduchu. Smyslem této studie bylo posoudit projevy a realizaci respiračních manévrů na axiální systém, především hrudní a abdominální oblast. Během experimentu byly sledovány rozdíly v reakci hrudníku a břicha při respiračním manévru ve směru vertikálním, předozadním a laterálním. Rozdílnost v těchto ukazatelích při jednotlivých fázích respiračního manévru nám potvrzuje předpoklad možnosti ovlivnění vybraných složek axiálního systému prostřednictvím vhodně zvoleného respiračního manévru. Po zpracování výsledků měření byla zjištěna výrazná převaha realizovaného pohybu v oblasti břicha oproti regionu hrudníku, i když zde má pohyb více charakter 3D, který je dán kinematickým pohybem žeber do stran. Pohyb je tedy prostorově komplexnější. Spirometrické vyhodnocení zjištěných objemů je v souladu s naměřenými změnami tvaru trupu. Celkově je nutné hodnotit výsledky ne statisticky, ale kazuisticky - porovnávat vždy "vzorec" realizace daného dechového manévru danou osobou.